2014
DOI: 10.1038/hdy.2014.70
|View full text |Cite
|
Sign up to set email alerts
|

Genetic reincarnation of workers as queens in the Eastern honeybee Apis cerana

Abstract: Thelytokous parthenogenesis, or the asexual production of female offspring, is rare in the animal kingdom, but relatively common in social Hymenoptera. However, in honeybees, it is only known to be ubiquitous in one subspecies of Apis mellifera, the Cape honeybee, A. mellifera capensis. Here we report the appearance of queen cells in two colonies of the Eastern honeybee Apis cerana that no longer contained a queen or queen-produced brood to rear queens from. A combination of microsatellite genotyping and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This subspecies, like most other honey bee (sub)species is arrhenotokous (for some rare exceptions see Mackensen, 1943;DeGrandi-Hoffman et al, 1991;Holmes et al, 2015). Thus, when queenless Scutellata workers lay eggs they develop as haploid males (Hepburn and Crewe, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…This subspecies, like most other honey bee (sub)species is arrhenotokous (for some rare exceptions see Mackensen, 1943;DeGrandi-Hoffman et al, 1991;Holmes et al, 2015). Thus, when queenless Scutellata workers lay eggs they develop as haploid males (Hepburn and Crewe, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of thelytokous parthenogenesis in European-derived Apis mellifera virgin queens after becoming queenless, can produce rare females among a majority of male-destined eggs (Gloag et al 2017), including females that are reared as queens (Holmes et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In social Hymenoptera, thelytoky can occur in queens or workers and has profound consequences for the kin structure of insect societies. For example, worker thelytoky means that unmated laying workers can be genetically reincarnated as the next queen, increasing the potential for reproductive conflict between sisters (Greeff 1996a, b;Oldroyd 2014, 2018;Holmes et al 2014). Reincarnation means that the benefits of reproductive cheating by thelytokous workers are far greater than for arrhenotokous workers that can only produce males (Greeff 1996a, b;Beekman and Oldroyd 2008;Goudie and Oldroyd 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This study has shown that A. cerana workers are at least sometimes capable of thelytoky, as thelytoky by workers is the most parsimonious explanation for the origin of the contents of emergency queen cells (Figure 1) found in some of the colonies (Holmes et al, 2014b).…”
Section: What About Thelytoky?mentioning
confidence: 99%
“…From an ecological perspective, one of the most significant findings of this thesis is that some A. cerana workers are capable of thelytoky (Holmes et al, 2014b). If thelytokous reproduction is rare in A. cerana, could it be that some thelytokous lineages invaded the Solomon Islands, New Guinea and then Australia?…”
Section: Investigating the Potential Effects Of Thelytoky In Invasivementioning
confidence: 99%